2016
DOI: 10.3928/01477447-20160427-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Instrumented and Noninstrumented Surgical Treatment of Severe Vertebral Osteomyelitis

Abstract: The purpose of this study was to compare the outcomes of instrumented versus noninstrumented (decompression) surgical treatment of vertebral osteomyelitis. The study population included 104 patients with spinal osteomyelitis who were treated at the authors' institution between 2004 and 2012. This included 62 men and 42 women who underwent either instrumented (n=57) or noninstrumented (n=47) surgery. Mean patient age was 59 years, and mean follow-up was 38 months (range, 12-78 months). Specifically, the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…During PVO treatment, significant bone loss occurs directly by causative organisms and indirectly by disuse-type bone loss 3335 . Such bone loss can induce structural instability, which leads to neurological deficit, spinal deformity, and even death 36,37 . Therefore, permanent, and extensive stabilization using spinal instrumentation is often required after debridement or neural decompression.…”
Section: Discussionmentioning
confidence: 99%
“…During PVO treatment, significant bone loss occurs directly by causative organisms and indirectly by disuse-type bone loss 3335 . Such bone loss can induce structural instability, which leads to neurological deficit, spinal deformity, and even death 36,37 . Therefore, permanent, and extensive stabilization using spinal instrumentation is often required after debridement or neural decompression.…”
Section: Discussionmentioning
confidence: 99%
“…5 Arnold et al 23 observed that in patients with successful surgical treatments, 32% had an anterior approach, 24% had a posterior approach, and 44% had a combined approach. Pourtaheri et al 29 observed that in patients with instrumented surgical treatment, 58% had an anterior approach, 13% had a posterior approach, and 29% had a combined approach. While our rates for the anterior approach seem to align with previous literary reports, our high posterior-approach rates seem to be discrepant.…”
Section: Discussionmentioning
confidence: 99%
“… 117 Spinal instrumentation can be successful after thorough debridement and concomitant antibiotic administration. 8 , 88 , 118 Apparently, staphylococcal infections may heavily colonise spinal rods covering them with a thick biofilm, whist only a few biofilm-covered colonies of Mycobacterium tuberculosis have been observed on stainless steel rods. These findings are in favour of anterior instrumentation at the time of surgical debridement, especially with titanium implants that have lower bacterial adherence.…”
Section: Surgical Treatmentmentioning
confidence: 99%